A simple tool to measure procedural restraint intensity in children: validation of the PRIC (Procedural Restraint Intensity in Children) scale. Issue 8 (August 2019) - Lombart, Bénédicte; Annequin, Daniel; Cimerman, Patricia; De Stefano, Carla; Perrin, Odile; Bouchart, Celine; Schommer, Marie-Claire; Ramelot, Laura; Petit, Céline; Fournier-Charriere, Elisabeth; Caron, Anne; Trebosc, Solène; et al.
Abstract: Purpose: Restraint is often used when administering procedures to children. However, no metrologically scale to measure the restraint intensity had yet been validated. This study validated the metrological criteria of a scale measuring the restraint intensity, Procedural Restraint Intensity in Children (PRIC), used during procedures in children. Design and methods: The PRIC scale performance was measured by a group of 7 health professionals working in a children's hospital, by watching 20 videos of health care procedures. This group included 2 physicians, 1 pediatric resident, and 4 nurses. The intra-class correlation coefficients were calculated to evaluate the inter-rater and test-retest reliability and the construct validity with the correlation between PRIC scale and a numerical rating scale. Results: One hundred and forty measurements were made. Inter-rater and test-retest correlation coefficients were 0.98 and 0.98, respectively. The 2 scales were positively correlated with a Spearman coefficient of 0.93. Conclusions: This study validated the Procedural Restraint Intensity in Children (PRIC) scale in metrological terms with some limitation. However, there is not gold standard scale to precisely validate the reliability of this tool and this study has been conducted in "experimental" conditions. Nevertheless, this is the first scale measuring the intensity of physical restraint with a metrological validation. The next step will be to validate it in real clinical situations.